Diseño de un modelo operativo de logística para la compañía de transporte Flores Almendaríz e hijos Cía. Ltda. dedicada al transporte de carga pesada de la ciudad de Quito, con aplicación a pymes - Ávila Ávila, Sandra Elizabeth (2015)
Current project is aimed to structure an operating model so that Compañía de Transportes Flores Almendariz e Hijos Cia. Ltda. enhances its costs and make a better control on its profitability, as well as implement management of new routes to help new customers getting access. Flores Almendariz e Hijos Cia. Ltda. was established 8 years ago, approximately; during such time, deficiency to generate operating strategies has been noticed. As a part of the operating model, we have proposed to train the administrative and operating personnel; expansion in the marketing system; new procedures to calculate costs of trips, pursuant to diverse already established routes. We have performed a global survey of the enterprise and marketing, in order to identify the status of the company in comparison to other transportation enterprises, as well as possible new customers for already established routes. Besides, we have jointly worked with administrative executives of the enterprise to track new routes.